Critical and alternative approaches to leadership learning and development. Issue 1 (February 2013) - Edwards, Gareth; Elliott, Carole; Iszatt-White, Marian; Schedlitzki, Doris
This article is the introduction to the special issue on 'Critical and Alternative Approaches to Leadership Learning and Development'. This article reviews the past approaches to researching and theorising about leadership learning and development and proposes a shift towards critical and alternative approaches. This article then describes the various articles in the special issue and how they contribute towards this paradigm shift.